Luka Bakar: Epidemiologi, Patofisologi Dan Faktor Faktor Yang Mempercepat Penyembuhannya - Muhamad Djamil Alviando Arja; Syazili Mustofa (Medula, 2026)
Burn injuries are a type of injury that can be life-threatening and cause extensive tissue damage, requiring proper treatment to prevent complications and accelerate healing. The healing process of burn injuries involves complex biological mechanisms that are influenced by various factors, including inflammatory mediators, immune cells, and tissue components. This study aims to examine the epidemiology of burns, explain the pathophysiological process, and identify factors that can accelerate healing. The research method used is a literature review by searching scientific articles from PubMed, ScienceDirect, Google Scholar, and the Cochrane Library using keywords related to burn injury, pathophysiology, wound healing, and healing factors. The review results show that burns are more common in the productive age group, with the most common causes being fire, hot water, and electric current. The pathophysiology of burns includes the phases of hemostasis, inflammation, proliferation, and remodeling, all of which are influenced by the complex interaction of various cellular and molecular mediators. Several factors have been proven to accelerate wound healing, such as the active compounds in tobacco (flavonoids, tannins, saponins, and alkaloids), adequate nutrition, proper wound care management, and the patient's overall health condition. Understanding the epidemiology, pathophysiology, and healing factors of burn wounds is crucial for improving patient management quality and can serve as the basis for developing more effective and safer therapies.